Air Quality in the Northern Colorado Front Range Metro Area: The Front Range Air Pollution and Photochemistry Éxperiment (FRAPPÉ). Issue 2 (20th January 2020) - Flocke, Frank; Pfister, Gabriele; Crawford, James H.; Pickering, Kenneth E.; Pierce, Gordon; Bon, Daniel; Reddy, Patrick
Abstract: We describe the resources used, the deployment strategy, and the outcomes of the Front Range Air Pollution and Photochemistry Éxperiment (FRAPPÉ) experiment, which took place in the summer of 2014 in the Front Range of Colorado. We provide a history of air quality of the region and the outcomes of previously conducted experiments, describe the atmospheric conditions encountered during the campaign, and summarize the scientific findings that the campaign produced, together with the Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER‐AQ) intensive, simultaneously carried out by the National Aeronautics and Space Administration. The goal of FRAPPÉ was to measure emission tracers and photochemical tracers from the ground and by aircraft to be able to quantify the contributions of various emission sectors to the photochemical production of ozone in the Colorado Front Range. We found major contributions from the fossil fuel extraction sector as well as the transportation sector, with minor contributions from agriculture, energy generation, and industry. The meteorological conditions were also found to be critical in creating situations conducive to high ozone in the area. Key Points: We describe the deployment and the outcomes of the FRAPPÉ experiment, which took place in the summer of 2014 in the Front Range of Colorado The goal of the campaign was to quantify the contributions of various emission sectors to ozone produced in the region Major contributors to photochemical ozone production were identified as emissions from transportation and from the oil and gas sector. Meteorological conditions were also found to be critical for high‐ozone episodes